Management of Common Postpartum Problems - Sugarman, Robert G. (1984)
Difficulties in the postpartum period detract from new parents' enjoyment of their child. Practical approaches to episiotomy care, timing of discharge from hospital, breast-feeding and drugs, bladder dysfunction, fever, depression, vaginal bleeding, contraception and the `postpartum check' assure continuing good health of the new mother. The art and science of medicine must be judiciously mixed with knowledge, compassion and reassurance.